Coexistent psychopathologies in essential tremor patients: The effect of pharmacological treatment of coexistent pathologies to tremor severity - (:unkn) unknown (My University, 2001)
Objective: Psychiatric evaluation of 50 essential tremor (ET) patients was performed to determine the coexistent psychopathologies. The patients with positive psychopathologies were intended to treat by appropriate medication to demonstrate a positive effect of the treatment to tremor severity. Methods: Symptom check list (SCL-90R) and structural clinical interview-nonpatient (SCID-NP) were used as screening tests for psychopathologic symptoms. The patients with positive psychiatric findings according to DSM IV criteria were asked to use appropriate medication for 6 weeks in addition to their antitremor drugs. Alprazolam 0.75 mg daily was used for generalized anxiety disorder and social phobia, and sertraline 50 mg daily was given for affective disorder. Tremor severity was assessed by a standard scale before and after treatment. Results: The results revealed the presence of anxiety disorder in 42%, social phobia in 18%, and affective disorder in 16 % of the patients. Administration of alprazolam to patients with anxiety disorders demonstrated a statistically significant improvement in tremor severity (p<0.05), however, in patients with social phobia and affective disorders no significant improvement was observed after alprazolam or sertraline treatment, respectively. Conclusion: Although the present study lacked a post-treatment psychiatric evaluation and had a limited study period of 6 weeks to identify the effect of present psychopathology on tremor severity, the observed frequent coexistence of psychopathologies and ET was quite remarkable. The results reinforced the positive effect of alprazolam on tremor control of ET patients with anxiety disorder. However, we could not demonstrate a significant improvement in tremor severity following treatment in ET patients having social phobia or dysthimic symptoms.
Keywords: Coexistent; Essential tremor; Psychopathology; Treatment